The Effect of Identification and Management of Dental Health Problems on Kindergarten and Elementary School Teachers Knowledge Levels in Keputih Public Health Center (Puskesmas) - Siswanto, Secondini Hillary; Abraham, Janery Fidelia; ‘Aini, Nisrina Qurrota; Damayanti, Meidy; Wulansari, Ananta Ayu; Aprilia, Vina; Guna, I Dewa Agung Wirya; Sary, Hikmah Putri; Nabella, Tamima Izzat; Jatiatmaja, Nabilah Azzahra; Setijanto, R. Darmawan (Indonesian Journal of Dental Medicine, 2019)
Background: Caries is a common dental and oral health problem. Caries is one of the serious health problems for school children, especially elementary school children. Primary school-age children are susceptible to dental and oral health problems due to lack of knowledge, and they are still unable to maintain oral and dental health. The level of teacher's knowledge about dental and oral health influences students' attitudes and behavior regarding dental and oral health. Purpose: To identify the effect of identification and management of dental health problems empowerment program on kindergarten and elementary school teachers' knowledge in Keputih public health center (Puskesmas). Methods: This was an analytic observational study with a cross-sectional approach. The population was a kindergarten and elementary teachers in Keputih. Results: The result showed an increase in teachers' knowledge from 50% to 72.5% after the intervention. Conclusions: The program concluded that there was an increase in teachers' knowledge levels regarding the identification and management of resolving dental health problems.